Aplikasi Bioinsektisida Beauveria bassiana dan Pupuk Kotoran Ayam dalam Mengurangi Serangan Hama Scotinophora coarctata pada Tanaman Padi: Application of Bioinsecticide Beauveria bassiana and Chicken Manure in Reducing Scotinophora coarctata Pest Attack on Rice Plant - Sumini Sumini; Novianto Novianto (Politeknik Negeri Lampung, 2021)
The aim of this study was to determine the level of S. coarctata pest attack on rice plants applied with B. bassiana bioinsecticide and chicken manure. The research was conducted in Musi Rawas Regency from January to May April 2017. The identification of arthropods was carried out at the Pest and Disease Laboratory, Faculty of Agriculture, Musi Rawas University. This study used an experimental method with a factorial randomized block design (RBD), which consisted of 2 treatment factors and was repeated 3 times. The results of the analysis of diversity showed that the application of bioinsecticide (B) and the treatment of manure (K) had a very significant effect on the observation of the level of damage due to S. coarctata attacks, while the interaction between the application of bioinsecticide and manure had no significant effect. The lowest level of damage was found in treatment B1 which was 3.87% and the highest was in treatment B0 which was 6.42%. For the treatment of livestock manure, the lowest level of damage was K1, namely 4.3% and the highest level of damage was K3 treatment, namely 5.24%. Whereas for treatment interactions, the lowest level of damage was found in the B1K1 combination, namely 3.37% and the highest in the B0K3 treatment combination, namely 7.4%. Keywords: bioinsecticide, chicken manure, Scotinophora coarctata